Global Transcriptional Profiling of the Cyanobacterium Chlorogloeopsis fritschii PCC 9212 in Far-Red Light: Insights Into the Regulation of Chlorophyll d Synthesis - Ho, Ming-Yang; Bryant, Donald A. (Frontiers in Microbiology, 2019)
Unlike plants and most algae that use visible light for photosynthesis, some terrestrial cyanobacteria can acclimate to and then utilize far-red light (FRL;  = 700-800 nm) to perform oxygenic photosynthesis through a process called Far-Red Light Photoacclimation (FaRLiP). During FaRLiP, cells synthesize chlorophylls (Chl) d and Chl f and extensively remodel their photosynthetic apparatus by modifying core subunits of photosystem (PS)I, PSII, and the phycobilisome (PBS). These changes allow cyanobacteria to absorb FRL for oxygenic photosynthesis and growth. Three regulatory proteins, RfpA, RfpB, and RfpC, are encoded in the FaRLiP gene cluster; they sense FRL and control the synthesis of Chl f and expression of the FaRLiP gene cluster. However, it was previously uncertain if Chl d synthesis and other cellular changes to FRL were regulated by RfpABC. In this study, we show that Chl d synthesis is regulated by RfpABC, but that most other transcriptional changes are not regulated by RfpABC. Surprisingly, erythromycin induces Chl d synthesis in vivo. Transcriptomic and pigment analyses indicate that thiol compounds and/or cysteine proteases could be involved in Chl d synthesis in FRL and that the protein(s) responsible for Chl d synthesis is/are probably encoded in the FaRLiP gene cluster. Transcriptional responses to FRL help cells to conserve and produce energy and reducing power to overcome implicit light limitation of photosynthesis during the initial acclimation process to FRL.